An analysis of the impact of the COVID-19 pandemic on the number of tourists arriving in Romania using the correspondence factor analysis - Aivaz, Kamer-Ainur; Micu, Adrian (Technium Social Sciences Journal, 2021)
Due to the restrictions imposed during the COVID-19 pandemic, but also to the reluctance of the consumers to travel, tourism is one of the most affected sectors worldwide. Romania was no exception to this truth, as most vacations were canceled, and travel budgets were cut. However, Romanians have not lost their appetite for travel, opting, as will be seen in this study, for holidays in their own country, for destinations as close to home as possible, with the possibility of canceling without a penalty. Those who chose foreign destinations preferred Bulgaria, Greece or Turkey. This paper aims to carry out a dynamic analysis of the number of tourists arriving in Romania in the 2018-2020 period by two distinct categories: Romanian tourists and foreign tourists, and to identify the links between the statistical variables: year and region. Our conclusion was that 2020 was the year of the rediscovery of Romania by Romanians, this pandemic representing a chance to reposition our country among European destinations.